Antioxidant and hepatoprotective effects of Lithocarpus polystachyus against carbon tetrachloride-induced injuries in rat - Li, Shenghua; Zeng, Junying; Tan, Juan; Zhang, Jian; Wu, Qifan; Wang, Lingpeng; Wu, Xianjin (Bangladesh Journal of Pharmacology, 2014)
The present study aims to investigate the hepatoprotective and antioxidant effects of the total flavonoid of Lithocarpus polystachyus Rehd.(LP-F) in vitro and in vivo. The in vitro anti-oxidant property of total flavonoids was investigated by employing various established systems. Rats with carbon tetrachloride-induced liver injury were used to assess the hepatoprotective and anti-oxidant effect of total flavonoids in vivo. The level of activity of glutamate pyruvate transaminase, aspartate aminotransferase, alkaline phosphatase and gamma-glutamyl transpeptidase, total bilirubin, total cholesterol, triglycerides total protein and albumin contents in the serum and malondialdehyde, superoxide dismutase, catalase, and glutathione in the liver and kidney of the rats were assayed using standard procedures. The results showed the total flavonoids of L. polystachyus has strong hepatoprotective and anti-oxidant activity in vitro and in vivo. These data were supplemented with histopathological studies of rat liver sections. This suggests that the hepatoprotective activity of formulation is possibly attributed to its free radical scavenging properties.